Pengaruh Pendapatan Perkapita dan Belanja Fungsi Kesehatan Daerah Terhadap Angka Harapan Hidup di 27 Kabupaten atau Kota Provinsi Jawa Barat Tahun 2018-2023 - Kharisya, Namira; Hariani, Ermatry (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of per capita income and health function expenditure on life expectancy in 27 regencies/cities in West Java Province from 2018 to 2023. The research employs a quantitative approach with a panel data method and regression analysis using Eviews 12 software. Data were sourced from the Central Statistics Agency and the Ministry of Health, covering all administrative areas in West Java as the sample population. The results indicate that both per capita income and health function expenditure have a positive and significant effect on life expectancy. These findings suggest that improvements in community welfare and allocation of health budget can enhance life expectancy levels in the region. The implication of this study emphasizes the importance of data-based health development policy planning to support the enhancement of community quality of life.